New bioimaging avenues for organs‐on‐chips by integration of bioluminescence. Issue 6 (23rd July 2021) - Moreira Teixeira, Liliana; Mezzanotte, Laura
Abstract: The unmet demand for the development of advanced in vitro models that emulate key features of human (patho‐)physiology and organ or tissue functionality led to the emergence of organ‐on‐a‐chip screening platforms. This biomimetic microtechnology enables accurate prediction of human responses, even at the multitissue or organ interaction level. With these advances, the necessity of incorporating biosensing within these platform becomes increasingly evident, to ultimately allow in situ, noninvasive, monitoring of cells, tissues and organs' behavior. Seamlessly integrated biosensors on‐chip also offer the prospect of uninterrupted and fully automated analysis. The continuous search for biosensors that not only avoid disruptive analyses, but are also highly sensitive and permit instant in situ evaluation, steered further developments of optical biosensors including bioluminescence (BL). BL is particularly suitable to interrogate biological systems at the multiparameter level and it is well matched to address the intrinsic biological systems' heterogeneity due to its inherent high signal to background ratio, to which the demand of simple measurement equipment can be added. Moreover, BL can be effortlessly integrated into any available organ‐on‐a‐chip platform and provides unique groundbreaking means for online monitoring, at the cellular level, and/or detection of cell secreted/excreted compounds. This review depicts recent advances in biosensors, with particular focus on BL. We highlight current challenges and future directions, aimed at stimulating the application of BL to interface organ‐on‐a‐chip systems, leading to the exponential advancement of both fields. Abstract : The integration of organ‐on‐a‐chip models with biosensors, in particular based on bioluminescence (BL), uniquely enables online, real‐time and non‐invasive monitoring of cellular events, with an unprecedent balance of sensitivity of detection, multiplexing, cost effectiveness and easiness of use. Here, we highlight the potential of combining BL strategies with organ‐on‐a‐chip systems, focusing on applications and anticipated advancements, expected increase the speed and efficacy of sensing key biological events. In turn, such innovative complementary technologies hold the promise to improve our understanding of human diseases, drug development and patient‐specific therapy screening.